Comparative Musicology and Anthropology of Music: Essays on the History of Ethnomusicology - Nettl, Bruno; Bohlman, Philip V. (Chicago The University of Chicago Press, 1991)
Nineteen scholars from five countries explore significant issues in the history of ethnomusicology and its methodological and theoretical foundations, while providing a critique of the discipline."This is a useful and enriching collection of articles of interest to musicologists and ethnomusicologists. . . . The authors manage to cover much ground, presenting fascinating insights into the history of the discipline while also exploring new directions in both theory and analysis. . . . the most sweeping work of this kind to be published since the 1960s."L. D. Loeb, University of Utah, for Choice
Keywords: Ethnomusicology